Revolusi Gaya Belajar untuk Fungsi Otak - Waluyo, M. Edy (Nadwa, 2014)
This paper elaborate on an attempt to maximize the function of brain as a form of learning revolution. Learn properly is not an issue of whether or not a student pass the test. The meaning of learn is broader than a success of passing the ex-ams. This is certainly related to the fun learning during the process of maximiz-ing the ability to achieve success. Each student has a different learning styles depending on his/her character. There are four different models of learning that has been known today, ie sketch, sound, tactics, and movement. Students who have studied the model using the sketch tends to be easier to understand the in-formation that they see. While those who have learned how to use the sound tends to be easier to capture verbal information from the teacher. Students who have a tendency to learn with tactics models require a touch of emotion. The kinesthetic learning models require movement in the learning process so that children learn more successfully.AbstrakTulisan ini menguraikan upaya memaksimalkan kerja sebagai bentuk revolusi belajar. Belajar dengan benar bukan permasalahan tentang lulus atau tidaknya seorang siswa dalam ujian. Makna belajar lebih luas daripada sekedar dapat lulus ujian. Hal ini tentu berhubungan dengan pembelajaran yang menyenangkan selama proses memaksimalkan kemampuan untuk meraih kesuksesan. Setiap siswa mempunyai cara belajar yang berbeda-beda tergantung karakter masing-masing siswa. Ada empat macam model belajar yang telah dikenal saat ini, yaitu gambar, suara, taktik, dan gerakan. Siswa yang mempunyai model belajar menggunakan gambar cenderung akan mudah memahami informasi yang telah dilihat. Sementara mereka yang mempunyai cara belajar menggunakan suara cenderung akan mudah menangkap informasi verbal dari guru. Siswa yang mempunyai kecenderungan belajar dengan model taktik memerlukan sentuhan emosi. Adapun model belajar kinestetik menuntut gerakan dalam proses pembelajaran sehingga belajar anak lebih berhasil.